Associations between parent-child relationship, self-esteem, and resilience with life satisfaction and mental wellbeing of adolescents - Trong Dam, Vu Anh; Do, Ha Ngoc; Thi Vu, Thao Bich; Vu, Khanh Long; Do, Hoang Minh; Thi Nguyen, Nga Thu; Nguyen, Tham Thi; Thi Vu, Thuc Minh; Thi Nguyen, Thao Phuong; Auquier, Pascal; Boyer, Laurent; Fond, Guillaume; et al. (Frontiers in Public Health, 2023)
Purpose: Mental well-being and life satisfaction play an important role in the development of adolescents, yet factors potentially influencing these states have not been sufficiently studied, especially in Vietnam. This study aims to fill the research gaps by exploring the associations of the parent-child relationship, self-esteem, and resilience on the mental well-being and satisfaction with life of adolescents. Methods: A cross-sectional study was conducted from June to July 2020 on 1023 adolescents from 10 to 18 years old living in Vietnam. To assess the satisfaction with life as well as the mental well-being of participants, this study used the Satisfaction with life and The World Health Organization- Five Well-Being Index scale. Results: More than 70% of participants reported having conflicts with their parents (74.6% of those conflicted with their father ad 73.9% of those conflicted with their mother), while 26.3% stated dissatisfaction with life. The mean score of mental well-being was 61.5 (SD = 23.0). Higher academic performance, self-esteem, resilience, encounter loneliness and isolation within own family, and having support and sharing from family members had a positive effect on life satisfaction and mental well-being. Female participants had higher satisfaction with life score (Coef = 0.77; 95%CI = 0.10; 1.44) but they had a lower mental well-being score (Coef = -6.00; 95%CI = -8.57; -3.44) than male participants. High school students had lower both satisfaction with life and mental well-being scores than secondary students. Conclusion: The results highlight the importance of being aware of the influence that expectations (of higher grades) and bias (towards male children) imposed by parents, teachers, and society on the mental well-being of youths, especially in Asian cultures. Strengthening the family bond and encouraging young people to share their feeling is also crucial to enhancing the mental health condition of adolescents.